Constitutional Implications of Local Government Restrictions on the Validity of Religious Legal Entity Deeds - Iman Jalaludin Rifa’i; Erga Yuhandra; Fatur Faturohman (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study examines the constitutional limits of regional government authority in restricting religious activities and analyzes their implications for legal certainty concerning religious deeds and permits. Although decentralization grants substantial administrative discretion to local governments, constitutional guarantees under the 1945 Constitution require that any limitation on religious freedom comply with legality, necessity, and proportionality standards. Normative inconsistencies arise when regional regulations introduce additional procedural burdens or discretionary mechanisms that exceed statutory delegation and potentially undermine constitutional supremacy. This research employs normative legal methodology through statute, conceptual, and case approaches by examining constitutional provisions, regional governance legislation, and relevant Constitutional Court decisions. Legal materials are analyzed qualitatively using constitutional reasoning, hierarchical norm conformity review, and proportionality assessment. The findings indicate that the constitutional boundary of regional authority lies in strict adherence to proportionality parameters, including legitimate aims, suitability, necessity, and balancing. Furthermore, regional restrictions have significant implications for administrative legal certainty, particularly regarding the issuance of religious permits and the enforceability of related civil documentation. Regulatory fragmentation and inconsistent procedural standards risk generating unequal treatment and indirect limitations on religious freedom. The novelty of this research lies in integrating proportionality doctrine with administrative legal certainty analysis, offering a constitutional design model that harmonizes regional autonomy with fundamental rights protection without negating legitimate local governance functions.